miR-221 suppression through nanoparticle-based miRNA delivery system for hepatocellular carcinoma therapy and its diagnosis as a potential biomarker - Li F (Dove Medical Press, 2018)
Feng Li,1,* Feiran Wang,2,* Changlai Zhu,3 Qun Wei,1 Tianyi Zhang,1 You Lang Zhou4 1Department of Gastroenterology, 2Department of General Surgery, Affiliated Hospital of Nantong University, 3Key Laboratory of Neuroregeneration, Nantong University, 4The Hand Surgery Research Center, Department of Hand Surgery, Affiliated Hospital of Nantong University, Nantong, Jiangsu, People’s Republic of China *These authors contributed equally to this work Background: MicroRNA-221(miR-221) is frequently dysregulated in cancer. The purpose of this study was to explore whether miR-221 can be used as a potential diagnostic marker or therapeutic target for hepatocellular carcinoma (HCC). Methods: In this study, we investigated whether miR-221 expression was associated with clinicopathological characteristics and prognosis in HCC patients, and we developed a nanoparticle-based miRNA delivery system and detected its therapeutic efficacy in vitro and in vivo. Results: We found that miR-221 was upregulated in HCC tissues, cell lines and blood of HCC patients. Upregulated miR-221 was associated with clinical TNM stage and tumor capsular infiltration, and showed poor prognosis, suggesting that its suppression could serve as an effective approach for hepatocellular carcinoma therapy. Treatment of HCC cells with nanoparticle/miR-221 inhibitor complexes suppressed their growth, colony formation ability, migration and invasion. In vivo, the growth of the tumors treated by the nanoparticle/miR-221 inhibitor complexes were significantly less than those treated by the nanoparticle/miRNA scramble complexes. In addition, circulating miR-221 may act as a potential tumor biomarker for early diagnosis of HCC, and combined serum miR-221 and AFP detection gave a better performance than individual detection in early diagnosis of HCC. Conclusion: These findings suggest that a nanoparticle-based miRNA delivery system could potentially serve as a safe and effective treatment and miR-221 could also be a potential diagnostic marker for HCC. Keywords: hepatocellular carcinoma, nanoparticle, miR-221, biomarker, therapeutic target